1999
DOI: 10.1007/bf02845529
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid and lipoprotein composition in infants of diabetic mothers

Abstract: Diabetes mellitus (DM) alters carbohydrate and lipid metabolism to a great extent. This study was planned to determine whether infants of insulin dependent and gestational diabetic mothers have abnormal lipid metabolism. Three groups of newborns were included in the study; group I consisted of 7 infants of diabetic mothers (IDM) with insulin dependent DM (Type 1 DM), group II of 18 infants of gestational diabetic mothers and group III of 20 control neonates whose mothers had no history of DM. Total cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Regarding the lipid profile, previous studies have showed a positive relationship between plasma LDL-cholesterol levels and paternal history of diabetes [ 16 ] and higher serum triglyceride levels in male offspring of T2D mothers than females of the same group [ 7 ]. Also, a study showed that diabetes in pregnant women causes a tendency to LDL hypercholesterolemia in the offspring [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lipid profile, previous studies have showed a positive relationship between plasma LDL-cholesterol levels and paternal history of diabetes [ 16 ] and higher serum triglyceride levels in male offspring of T2D mothers than females of the same group [ 7 ]. Also, a study showed that diabetes in pregnant women causes a tendency to LDL hypercholesterolemia in the offspring [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [50] have reported that VLDL and LDL-C concentrations are significantly elevated in newborns of mothers with gestational diabetes. Increased LDL-C levels have been reported recently [51] in infants of Type I and gestational diabetic mothers as compared with levels in control infants. High activities of LPL and hepatic TAG lipase (HTAGL) have also been reported in infants of diabetic mothers [52,53].…”
Section: Alterations In Lipid and Lipoprotein Levelsmentioning
confidence: 92%
“…In certain conditions, an unfavorable lipid pattern in children (1–2) and newborns (3–6) can be associated with an increased risk of subsequent cardiovascular disease.…”
mentioning
confidence: 99%